2015
DOI: 10.3847/2041-8205/816/1/l1
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION OF SHARP SYMMETRIC FEATURES IN THE CIRCUMBINARY DISK AROUND AK Sco*

Abstract: The Search for Planets Orbiting Two Stars (SPOTS) survey aims to study the formation and distribution of planets in binary systems by detecting and characterizing circumbinary planets and their formation environments through direct imaging. With the SPHERE Extreme Adaptive Optics instrument, a good contrast can be achieved even at small (<300 mas) separations from bright stars, which enables studies of planets and disks in a separation range that was previously inaccessible. Here, we report the discovery of re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
61
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 35 publications
15
61
1
Order By: Relevance
“…3 we also applied an unsharp mask to the polarized intensity in order to enhance the disk structure. Other doublearch structures in TDs have been recently reported with highcontrast imaging instruments such as SPHERE (Janson et al 2016;Garufi et al 2016;Pohl et al 2017), but spiral-like features such as the one observed here have not yet been detected in very inclined disks. The spiral-like features detected in the RY Lup disk images could be created by an interaction of the disk with a planet located in its surrounding (Dong et al 2016).…”
Section: Disk Propertiessupporting
confidence: 52%
“…3 we also applied an unsharp mask to the polarized intensity in order to enhance the disk structure. Other doublearch structures in TDs have been recently reported with highcontrast imaging instruments such as SPHERE (Janson et al 2016;Garufi et al 2016;Pohl et al 2017), but spiral-like features such as the one observed here have not yet been detected in very inclined disks. The spiral-like features detected in the RY Lup disk images could be created by an interaction of the disk with a planet located in its surrounding (Dong et al 2016).…”
Section: Disk Propertiessupporting
confidence: 52%
“…However, a deeper discussion is beyond the scope of the current paper. Broadly speaking, this doublewing structure is a new type of feature (see also AK Sco, Janson et al 2016) that may be recurrent among the observations of inclined disks carried-out with the new generation AO systems. Our exploration has shown that such a peculiar structure may still be interpreted in the context of a disk with an azimuthally continuous brightness distribution.…”
Section: Disk Morphology and Scattering Propertiesmentioning
confidence: 79%
“…Even though there is an astrometric orbit for the AK Sco binary (Anthonioz et al 2015), the model used for the interferometric fit included a narrow ring with radius ∼0.5 au to mimic the contribution from the inner edge of a circumbinary disk. Subsequent scattered light observations (Janson et al 2016;Dong et al 2016) and sub-mm observations (Czekala et al, in prep) revealed that the dust in AK Sco is actually distributed in a narrow ring with a radius of ∼30 au, raising the possibility that the stellar orbital parameters from the interferometric model could be biased. For the purposes of the hierarchical model, we ignore the AK Sco astrometric orbit and treat Ω and θ as unknown.…”
Section: Notementioning
confidence: 99%